Coordinated operation control on low DC voltage of HVDC integrating wind farms. Issue 16 (18th January 2019) - Zhang, Qingzhi; Zhao, Chenggong; Du, Chuan
Abstract : In recent years, with the development of high voltage direct current (HVDC) transmission technology, wind power integration with modular multiple converter‐HVDC (MMC‐HVDC) has been widely researched and applied. However, the conventional control methods on wind power integration cannot match the flexibility needing of loads. In this paper, a wind power integration system with permanent magnet direct‐drive wind farm and full‐bridge MMC is proposed. It has the characteristics of independent control of AC and DC current, which can realise the stable operation of the system under low DC voltage, so that to effectively avoid the accident of the wind turbine cut‐off caused by the load reduce. When the DC voltage drops, the system can maintain a constant AC voltage at the wind power integration point, so that the wind farm can operate normally. Finally, the simulation results in PSCAD/EMTDC show that the proposed system and its control strategy are correct.